Viewpoint: Students as Agents of Social Change- Student Initiatives at Rhodes University, South Africa - Muchateyi Togo (Environmental Association of Southern Africa, 2009)
Rhodes University has a diversity of sustainable development initiatives meant for students and in a range of cases activities are initiated by students themselves with the support of the university. Results of a sustainability assessment revealed the involvement of students in environmental societies, environmental awareness campaigns, campus sustainability initiatives and community sustainability projects. Though most of the projects are still in their infancy and some challenges are yet to be overcome, the sustainability initiatives are gaining momentum and have contributed to improving the overall picture of sustainability at the university. Based on the results of the Rhodes University case study, the underpinning viewpoint in this paper is that university students are not merely recipients of Education for Sustainable Development but have the capacity to become agents for social change.